Penerapan akuntansi lingkungan pada Rumah Sakit Umum Daerah Dr.Kanujoso Djatiwibowo Kota Balikpapan - Anam, Hairul; Ramlah, Ramlah (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2020)
The aim of building a hospital is to improve health service. As an educational institution of health and research source, a hospital has both negative and positive sides for the environment. The waste produced might be direct impact which is very dangerous for environment. A hospital should give attention and be responsible for that, because an environment has contribution for the hospital. A hospital is supposed to spend much money. This thesis aims to know the implementation of environmental accounting in reporting informative financial report and to know the responsibility of environment at District Hospital of RSUD dr.Kanujoso Djatiwibowo Balikpapan relating to hospital waste mangement. This research employs descriptive qualitative design and District Hospital of RSUD dr.Kanujoso Djatiwibowo Balikpapan is used as the object of this research. This research involved staffs in the hospital who are dealing with environmental fee, for instance: planning, finance and sanitation staff. The result of this research shows that District Hospital of RSUD dr.Kanujoso Djatiwibowo Balikpapan controls hospital waste management properly. It was proven by not having external fee. To implement environmental accounting, hospital stakeholders haven't implemented it. The researcher identified, classified, and proposed environmental fee report. From the report, all of environmental fee could be transparantly seen.Â  It makes the staffs easy to control all parts of hospital waste.